Harmol induces autophagy and subsequent apoptosis in U251MG human glioma cells through the downregulation of survivin - ABE, AKIHISA; KOKUBA, HIROKO (Oncology reports, 2013)
The β-carboline alkaloids are plant substances that exhibit a wide spectrum of neuropharmacological, psychopharmacological and antitumor effects. In the present study, we found that harmol, a β-carboline alkaloid, induced autophagy and suppression of survivin expression, and subsequently induced apoptotic cell death in U251MG human glioma cells. Autophagy was induced within 12 h by treatment with harmol. When treated for over 36 h, however, apoptotic cell death was induced. Harmol treatment also reduced survivin protein expression. Small interfering RNA (siRNA)-mediated knockdown of survivin enhanced the harmol-induced apoptosis. Knockdown of survivin by siRNA also induced autophagy. Therefore, harmol-induced apoptosis is a result of the reduction in survivin protein expression. Treatment with 3-methyladenine (3-MA) in the presence of harmol did not affect the expression of survivin and diminished harmol-induced cell death. Treatment with chloroquine in the presence of harmol did not suppress the reduction of survivin expression and increased harmol-induced cell death. From these results, harmol-induced reduction of survivin expression was closely related to autophagy. It is assumed that when isolation membrane formation is inhibited by treatment with 3-MA, reduction of survivin protein expression and apoptotic cell death were not induced. However, when isolation membrane formation is started and an autophagosome is formed, survivin expression is suppressed and apoptosis is executed. Harmol treatment reduced phosphorylation of Akt, mammalian target of rapamycin (mTOR) and its downstream targets p70-ribosomal protein S6 kinase and 4E-binding protein 1, resulting in induction of autophagy. Conversely, activation of the Akt/mTOR pathway inhibited harmol-induced autophagy and cell death. These findings indicate that harmol-induced autophagy involves the Akt/mTOR pathway. Taken together, autophagy induced by harmol represented a pro-apoptotic mechanism, and harmol suppressed the expression of survivin and subsequently induced apoptosis.